How to Become a Psychoanalyst: A Guide for Social Workers - Danielle J. Dronet; Bruce A. Thyer (International Journal of Psychotherapy Practice and Research, 2025)
Social work has its roots in the efforts of early twentieth-century charity organizations to reduce human suffering. This movement among charity workers of the era was founded in the search for theoretical knowledge that would illuminate effective treatment options for social ills and ultimately transform the provision of charity into social work. Coinciding with the birth of social work was the development of psychoanalysis (PA) as a tool for theorizing and treating mental illness. For many decades training in PA theory was common within social work graduate programs and many clinical social workers practice today psychotherapy informed by PA principles. However, clinical social workers were long excluded from enrolling in and graduating from psychoanalytic training institutes, a requirement for being able to say that one is a psychoanalyst and provides psychoanalysis. In 1985, a legal ruling asserted that psychologists and other qualified mental health professionals could not be excluded from enrollment in PA training programs. Since that watershed decision, although many social workers have gone on to enroll and graduate as psychoanalysts, the process whereby one can pursue this training path is unfamiliar to most social workers. We describe the current PA training landscape and describe the process on how a LCSW can become a legitimate psychoanalyst.
Keywords: Social work